Experiencing nursing education research: narrative inquiry and interpretive phenomenology - Lindsay, Gail M (Nurse researcher, 2006)
Narrative inquiry is emerging from higher education curriculum studies into nursing, and interpretive phenomenology is established in nursing education research. These two research methods are compared by subject matter, agent, method, data and outcome, using examples from nursing education research. This comparison facilitates a researcher's choice of method by showing what is revealed by each type of inquiry and how they differ.